Tyrosine phosphorylation of MyD88 adapter-like (Mal) is critical for signal transduction and blocked in endotoxin tolerance - O'NEILL, LUKE ANTHONY JOHN (American Society for Biochemistry and Molecular Biology, 2008)
Toll-like receptor 4 (TLR4) recognition of lipopolysaccharide triggers signalosome assembly among TLR4, sorting (e.g. MyD88 adapter-like (Mal)) and signaling (e.g. MyD88) adapters, initiating recruitment and activation of kinases, activation of transcription factors, and production of inflammatory mediators. In this study we examined whether tyrosine phosphorylation of Mal regulates its interactions with TLR4, MyD88, interleukin-1 (IL-1) receptor-associated kinase (IRAK)-2, and tumor necrosis factor receptor-associated factor (TRAF)-6 and is important for signaling. Overexpression of wild-type Mal in human embryonic kidney 293T cells induced its constitutive tyrosine phosphorylation and led to activation of p38, NF-?B, and IL-8 gene expression. Mutagenesis of Tyr-86, Tyr-106, and Tyr-159 residues within the Toll-IL-1 receptor domain impaired Mal tyrosine phosphorylation, interactions with Bruton tyrosine kinase, phosphorylation of p38, and NF-?B activation. Lipopolysaccharide triggered tyrosine phosphorylation of endogenous Mal and initiated Mal-Bruton-tyrosine kinase interactions in 293/TLR4/MD-2 cells and human monocytes that were suppressed in endotoxin-tolerant cells. Compared with wild-type Mal, Y86A-, Y06A-, and Y159A-Mal variants exhibited higher interactions with TLR4 and MyD88, whereas associations with IRAK-2 and TRAF-6 were not affected. Overexpression of Y86A- and Y106A-Mal in 293/TLR4/MD-2 cells exerted dominant-negative effects on TLR4-inducible p38 phosphorylation and NF-?B reporter activation to the extent comparable with P125H-Mal-mediated suppression. In contrast, tyrosine-deficient Mal species did not affect NF-?B activation when signaling was initiated at the post-receptor level by overexpression of MyD88, IRAK-2, or TRAF-6. Thus, tyrosine phosphorylation of Mal is required for adapter signaling, regulates Mal interactions with TLR4 and receptor signaling, and is inhibited in endotoxin tolerance.
PUBLISHED
Keywords: Biochemistry